Evaluating the impact of whole-class self-management and interdependent group contingency approaches on pupil engagement and disruptive behaviour - Bhana, Kamal (2017)
This study investigates the efficacy of two whole-class approaches to classroom management, self-management and interdependent group contingency, in a sample of 8-9 year olds in the UK.